SISTEM PEMELIHARAN TANPA PADAM DENGAN MENGGUNAKAN UNIT GARDU BERGERAK (UGB) DI UNIT PELAKSANA PELAYANAN PELANGGAN KRAMAT JATI - Muhammad Akbar Firmansyah; Reni Rahmadewi (Peneliti.net, 2023)
Carrying out maintenance on the distribution network is a series of actions or processes that aim to maintain the condition of the equipment so that it can function properly and prevent damage or disturbances that can interfere with the performance of the equipment. The focus of this study is on the maintenance of distribution substations by using a mobile substation unit that is synchronized with the substation to be carried out. The purpose of using this mobile substation unit is to avoid power outages or what is known as non-outage maintenance. Maintenance without blackout is the process of maintaining the substation without interrupting the supply of electricity to consumers. Where this maintenance is carried out in a state of tension. One of the distribution substation maintenance methods without blackouts is to transfer the customer load from the distribution transformer to the Mobile Substation Unit transformer. This research was conducted at PT. PLN (Persero) UP3 Kramat Jati by collecting data using the literature method, observation method, interview method. The results of this study found that PT. PLN (Persero) UP3 Kramat Jati performs two maintenance methods, namely preventive maintenance and corrective maintenance.